Correlation Between the Peak Nasal Inspiratory Flow and the Visual Analogue Scale Before and After Using a Nasal Decongestant - Teixeira, Rodrigo Ubiratan Franco; Zappelini, Carlos Eduardo Monteiro; Oliveira, Luana Gonçalves; Basile, Luciana Campoy Giro; Costa, Everardo Andrade da (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The measurement of the peak nasal inspiratory flow (PNIF) is easily and swiftly obtained, but hardly spread in Brazil though. On the other hand, the visual analogue scale (VAS) for nasal obstruction is a subjective measurement that can also be used.Objective: To evaluate the correlation between PNIF and VAS for nasal obstruction before and after occurring a change in the nasal patency caused by the topic vasoconstriction. Study outline: Non-randomized clinical and experimental study.Method: 60 volunteers, including patients, doctors, nurses and administrative assistants of the institution were submitted to PNIF and VAS examinations before and after the nasal vasoconstriction with oxymetazoline chloride at 0.05%.Results: The average value found for pre-vasoconstriction VAS was 4.1 and, for post-vasoconstriction, it was 2. This represented a 44% range between the measurements. With regard to PNIF values, the average found when measuring the vasoconstriction was 151 l/min and 178 l/min after vasoconstriction, showing a 20% increase. At the pre-vasoconstrictor moment, increasing a point in average VAS value corresponds to a 3.8% decrease in average PNIF value. In the post-vasoconstriction, each increase of a point in average VAS value corresponds to a 4.5% decrease in average PNIF value.Conclusion: There was an important correlation between the objective measurement of the nasal obstruction through PNIF and the subjective measurement provided by VAS before nasal vasoconstriction. A similar correlation could also be observed after using the decongestant.
Keywords: nasal obstruction; nasal cavity; nasal decongestants